Circulating inflammatory cytokines predict severity disease in hospitalized COVID-19 patients: A prospective multicenter study of the European DRAGON consortium - Barbara Polese; Marie Ernst; Monique Henket; Benoit Ernst; Marie Winandy; Makon-Sébastien Njock; Céline Blockx; Stéphanie Kovacs; Florence Watar; Anna Julie Peired; Sara Tomassetti; Cosimo Nardi; et al. (Elsevier, 2024)
Background: COVID-19 has put a huge strain on the healthcare systems worldwide, requiring unprecedented intensive care resources. There is still an unmet clinical need for easily available biomarkers capable of predicting the risk for severe disease. The main goal of this prospective multicenter study was to identify biomarkers that could predict ICU admission and in-hospital mortality. Methods: We prospectively recruited COVID-19 PCR positive patients in two hospitals, in Belgium and Italy. Blood samples were collected at hospital admission and 20 potential biomarkers were measured with the Luminex technology. Logistic regression models were performed to identify the biomarkers that, alone or together, were associated with patient disease severity. Results: Our study demonstrates that elevated levels of circulating inflammatory cytokines were associated with disease severity in COVID-19 hospitalized patients. CXCL10, IL-4, IL-6 and MCP-1 values were predictive of ICU admission. Elevated levels of IL-6 and MCP-1 were also associated with in hospital death in COVID-19 hospitalized patients. Conclusion: Altogether, elevated and correlated inflammatory cytokines in the blood of COVID-19 patients at hospital admission are predictive of disease severity and suggest a dysregulated inflammation induced by SARS-CoV-2 infection.